Dynamic space and time partitioning for yard crane workload management in container terminals - Guo, Xi (2013)
We propose a new hierarchical scheme for yard crane (YC) workload management in container terminals. We also propose a time partitioning algorithm and a space partitioning algorithm for deploying YCs to handle changing job arrival patterns in a row of yard blocks. The main differences between our approach and most of the methods in literature are (1) the average vehicle job waiting time instead of the number of jobs is used to balance YC workload and to evaluate the quality of a partition, (2) the YC working zone assignment is not in units of yard blocks and our space partitioning algorithm generates more flexible divisions of the workload from all blocks, and (3) the YC deployment frequency is not fixed but is decided by our time partitioning algorithm with the objective of minimizing average vehicle waiting times. The scheme combines simulation and optimization to achieve our objective for a row of yard blocks. Experimental results show that the proposed binary partitioning algorithm TP2 makes substantial improvements in job waiting times over the basic partitioning scheme and another existing algorithm (Ng, W. C. 2005. Crane scheduling in container yards with intercrane interference. Eur. J. Oper. Res. 164(1) 64–78) in all tested job arrival scenarios.